INTERRELATED PROCESSES OF DIGITALIZATION OF THE MODERN RUSSIAN SCIENCE AND EDUCATION - S. I. Nekrasov (Russian State Vocational Pedagogical University, 2018)
Introduction. The article was prepared in continuation of the discussion of the topical aspects of the reform of science and education in the Russian Federation, considered in the article by Professor I. P. Smirnov [1].The aim of the publication is to express criticism about the management methods in the Russian science and education.Methodology and research methods. The methods involve comparative analysis, generalization and synthesis.Results.The background of the "digitized society" formation is considered from the positions of educational practice. On the basis of specific examples, the author confirms the conclusions drawn by I. P. Smirnov about inadequacy of administratively imposed formalized qualimetric apparatus for objective assessment of the work of scientists and teachers, and that "digital indicators" (first of all - number of publications and the index of citing) set the false orientations which seriously prevent performance of scientific studies demanded by economy and society. The author provides a basis for a skeptical attitude towards the application of similar digitized technologies in education management. The possibility of operating with digital data at different levels does not enable to estimate the real educational results necessary for correction and planning of educational processes and, in general, for educational development. The consequences of introduction of quantitative criteria for measurement of scientific and pedagogical activity outcomes into science and education are shown. It is highlighted that it is important to take into account the opinions of scientists, teachers and the general public about the appropriateness of the commitment to the nationalization and administrative management of science and education.Practical significance. A number of proposals concerning the changes of existing approaches to the reform of science and education in the Russian Federation are brought forward: a revision of the leading indicators in the evaluation systems for scientific and educational activity effectiveness; a differentiated approach to the normative indicators of the activities of educational organizations regarding their status and other features; rejection of the use of bibliometrics as the main and exclusive tools for measurement of a scientists' ranking and a teacher's qualification; strengthening of the institute of peer reviewing of scientific publications; maximum reduction of the bureaucratic digital reporting requirements in science and education; etc.